UJI KOMPETENSI AGRIBISNIS TANAMAN PERKEBUNAN - Apriyanto, Mulono (Jurnal Agro Dedikasi Masyarakat (JADM), 2022)
One of the primary missions of Vocational High School is to prepare students to be candidates for labor who are ready to enter the workforce upon graduation. Schools should be able to prepare students in accordance with the National Education Standards in order to produce graduates who are internationally competitive in their fields. The implementation of a skill competency test is intended to assess the level of student achievement in a skill